Veteran and first responder family members show distinct mental health networks centered on negative emotions - Johannes A. Karl; Warren N. Ponder; Jose Carbajal; Oleg N. Medvedev (Communications Psychology)
Abstract The interplay of mental health symptoms among family members of veterans and first responders remains poorly understood despite their vital support role. Network analysis and community detection were performed on mental health assessment data from 317 treatment-seeking family members of trauma-exposed veterans and first responders, who completed clinical distress measures including posttraumatic stress disorder, depression, and anxiety. Network analysis revealed six distinct symptom communities: depression, generalized anxiety disorder, intrusion and avoidance, anxious arousal, externalizing behaviors, and negative alterations. Strong negative feelings (fear, horror, anger) and uncontrollable worry emerged as the most influential nodes in the network. Remarkably, 55.5% of participants screened positive for probable posttraumatic stress disorder, while 38.5% reported moderately severe to severe depression, and 36.6% experienced severe generalized anxiety disorder. The network demonstrated high stability across bootstrap analyses, with a correlation stability coefficient exceeding 0.59. Overall, this study revealed network of co-occurring mental health symptoms in family members of veterans and first responders. The identification of six distinct symptom communities suggests that traditional diagnostic boundaries may not fully capture the complexity of psychological distress in this population. These findings highlight the need for targeted interventions addressing both fear-based trauma symptoms and mood dysregulation in this understudied group.